"Glowing Gray" Does Exist: Luminance Gradients' Influence on Whiteness Perception. (July 2018) - Kobayashi, Yuki; Matsushita, Soyogu; Morikawa, Kazunori
Studies on brightness and lightness that employed luminance gradients (i.e., glare stimuli) have suggested that we can perceive luminosity even when the brightness target is darker than white . Although such studies had great impact on research in luminosity perception, whether the whiteness threshold in glare stimuli was lower or higher than the luminosity threshold remained unclear. This study indicated that it is higher than the luminosity threshold, confirming the existence of glowing gray . Moreover, we measured the luminance gradients' effect on whiteness perception but found no significant effect. Discrepancy in the degree of gradients' effect on perceived luminosity and perceived white suggests that different mechanisms underlie luminosity (brightness) perception and whiteness (lightness) perception.